A dialogue about teacher agency: Australian and Chinese perspectives. (October 2018) - Simpson, Alyson; Sang, Guoyuan; Wood, Julian; Wang, Yiting; Ye, Bixin
Abstract: Agency is emerging as a key concept, as part of increased debates about rigid accountability in measures of teacher effectiveness. However, the construct is elusive. Combining scholarship from Australian and Chinese scholars this research review undertook to create a dialogic space within which a geo-political position could be argued. Given recently introduced professional standards in China that shadow existing governance of teacher education in Australia, the findings indicate commonality in disparate contexts. We investigated how agency played out in the dynamic interplay of technologies of power and discovered the importance of exploring and representing teachers' work in an ecological framework. Highlights: Ecological concepts of agency provide impetus for debates on teacher professionalism. Comparative studies of professional standards reveal international policy drift. Tension arises in the dynamic interplay of individual empowerment and systemised controls in teaching. Agency is an epistemological stance on which teachers' work could be built.